Human Dignity, Life And Health And Access To Medically Assisted Procreation (Selected Comments) - Tykwińska-Rutkowska, Dominika (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
The subject of the analysis in this study is access to medically assisted procreation, in other words the right to treat infertility with the use of medically assisted procreation procedures, the principles, conditions and limits of which have been shaped out of concern for human dignity, life and health. The constitutional principles of dignity, protection of life and the right to protection of health, through the prism of which the analysis is carried out, are considered fundamental for determining access to medically assisted procreation procedures and, in connection with this, for determining the permitted scope of operations on reproductive cells and embryos.